PENERAPAN MODEL PEMBELAJARAN BERBASIS PORTOFOLIO UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS KELAS IV SDN JATIDUKUH I MOJOKERTO - Reninda Dewi Pinar (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2016)
The background of this research is begin with the student inactive in following subject that taught by teacher because teacher only applying same model on every learning activity, applying no learning model, and applying no learning media also have monotone teaching way so make student bore, lack communication between student and teacher, student only centered on teacher activity. Those matters causing the low of student learning result and still far from minimal completeness criterion as big as 70 especially on social study subject with main theme the development of production technology, communication and transportation and the experience of use it. The aims of this research are to describe student and teacher activity, improvement of student learning result and student respond on the application of based portfolio learning model on social study subject with main theme the development of production technology, communication and transportation and the experience of use it on fourth grade student of SDN Jatidukuh I Mojokerto. By applying portfolio based learning model student expected can understanding the matter holistically and obtained good learning result based on minimal completeness criterion since by applying portfolio based learning model can attracted student attention on learning so that they will not feel bore on learning activity. This research applying class action research that done in three cycles with research procedures such: planning, implementation, observation and reflection. Data analysis using descriptive qualitative method. Subject of this research is fourth grade student of SDN Jatidukuh I Mojokerto that amounted of 26 students. Data collection technique by using observation, evaluation test and interview. On learning activity, teacher activity experience improvement with percentage of first cycle as big as 69,64%, on second cycle is 86,90% and on third cycle as big as 97,61%. Student activity also experience improvement with percentage of first cycle as big as 64.40%, on second cycle is 72% and on third cycle as big as 91%. Student learning result on social study also experience mean improvement with percentage of first cycle as big as 60.61, on second cycle is 69.26 and on third cycle as big as 85.38. Thus, the application of portfolio based learning model can make student active and enthusiast in learning and can increase student learning result on social study on fourth grade student of SDN Jatidukuh I Mojokerto